SELinux by example using security enhanced Linux - Mayer, Frank 1961- (Prentice Hall, 2006)
SELinux: Bring World-Class Security to Any Linux Environment! € SELinux offers Linux/UNIX integrators, administrators, and developers a state-of-the-art platform for building and maintaining highly secure solutions. Now that SELinux is included in the Linux 2.6 kernel & mdash;and delivered by default in Fedora Core, Red Hat Enterprise Linux, and other major distributions & mdash;it & rsquo;s easier than ever to take advantage of its benefits. € SELinux by Example is the first complete, hands-on guide to using SELinux in production environments. Authored by three leading SELinux researchers and developers, it illuminates every facet of working with SELinux, from its architecture and security object model to its policy language. The book thoroughly explains SELinux sample policies & mdash; including the powerful new Reference Policy & mdash;showing how to quickly adapt them to your unique environment. It also contains a comprehensive SELinux policy language reference and covers exciting new features in Fedora Core 5 and the upcoming Red Hat Enterprise Linux version 5. € & bull; Thoroughly understand SELinux & rsquo;s access control and security mechanisms & bull; Use SELinux to construct secure systems from the ground up & bull; Gain fine-grained control over kernel resources & bull; Write policy statements for type enforcement, roles, users, and constraints & bull; Use optional multilevel security to enforce information classification and manage users with diverse clearances & bull; Create conditional policies that can be changed on-the-fly & bull; Define, manage, and maintain SELinux security policies & bull; Develop and write new SELinux security policy modules & bull; Leverage emerging SELinux technologies to gain even greater flexibility & bull; Effectively administer any SELinux system.
Includes bibliographical references and index. - Print version record
Keywords: Linux; Operating systems (Computers); Computer networks -- Security measures; Systèmes d'exploitation (Ordinateurs); Réseaux d'ordinateurs; Sécurité; Mesures; operating systems; Computer networks; Security measures